Upaya Meningkatkan Prestasi Belajar Siswa Melalui Penerapan Model Pembelajaran PBL Di SMAS Xaverius Gunungsitoli - Sergius Lay; Evimawati Harefa; Rikardo Gulo (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research is motivated by the low student learning achievement, this happens because the learning model used by the teacher is less attractive to students. This study aims to determine efforts to improve student learning achievement through the application of problem-based learning (PBL) learning models at St. Xaverius Gunungsitoli Private High School. This type of research uses descriptive qualitative research. The data collection techniques used are observation, interview and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The subjects in this study were teachers, students and principals. The results showed that the problem-based learning model was able to increase student activeness in the learning process, this is because teachers always give students the freedom to learn independently in the learning process. The conclusion is that the problem-based learning model is able to improve student learning achievement at SMAS Xaverius Gunungsitoli.